Analisis Pengaruh Jumlah Pengambilan Foto Dan Intensitas Cahaya Terhadap Penyimpangan Dimensi Model 3D Hasil Reverse Engineering Teknik Fotogrametri - M. Iqbal Adhitama; Wirawan Wirawan (Jurnal Kendali Teknik dan Sains, 2025)
Reverse engineering is the process of reproducing or recreating an existing model—whether it is a component, subassembly, or complete product—without relying on the original design documentation or CAD data. One of the key techniques that supports this process is photogrammetry, a method that utilizes a series of photographic images to identify, capture, and reconstruct the geometry of physical objects in three dimensions. Photogrammetry offers advantages such as low cost, portability, and non-contact data acquisition, making it a valuable tool in various engineering and industrial applications. This study aims to analyze the influence of two important factors—namely, the number of photographs taken and the intensity of lighting—on the dimensional accuracy or deviation of 3D models produced through photogrammetry-based reverse engineering. A quantitative experimental approach was used, where both variables were systematically varied to evaluate their effect on model precision. Data analysis was conducted using a Two-Way ANOVA factorial test to determine the statistical significance of each factor and their interaction. The experimental results revealed that using 54 photographs yielded the lowest average dimensional deviation among all tested conditions, although the difference was not statistically significant. Similarly, variations in light intensity showed no statistically significant effect on accuracy, but visually, an illumination level of 200–250 lux tended to provide more consistent and stable model outputs. No significant interaction was found between the two variables, indicating that they operate independently in affecting model accuracy. Overall, the combination of 54 photographs and a light intensity of 250 lux was visually identified as the most effective setup. The findings of this research contribute to the optimization of photogrammetry workflows in reverse engineering, offering practical insights for producing high-quality CAD models for use in design, prototyping, and manufacturing processes.